GlottisNetV2: Temporal Glottal Midline Detection using Deep Convolutional Neural Networks - Kruse, Elina; Döllinger, Michael; Schützenberger, Anne; Kist, Andreas (IEEE Journal of Translational Engineering in Health and Medicine, 2023)
Objective: High-speed videoendoscopy is a major tool for quantitative laryngology. Glottis segmentation and glottal midline detection are crucial for computing vocal fold-specific, quantitative parameters. However, fully automated solutions show limited clinical applicability. Especially unbiased glottal midline detection remains a challenging problem. Methods and procedures: We developed a multitask deep neural network for glottis segmentation and glottal midline detection. We used techniques from pose estimation to estimate the anterior and posterior points in endoscopy images. Neural networks were set up in TensorFlow/Keras and trained and evaluated with the BAGLS dataset. Results: We found that a dual decoder deep neural network termed GlottisNetV2 outperforms the previously proposed GlottisNet in terms of MAPE on the test dataset (1.85% to 6.3%) while converging faster. Using various hyperparameter tunings, we allow fast and directed training. Using temporal variant data on an additional data set designed for this task, we can improve the median prediction accuracy from 2.1% to 1.76% when using 12 consecutive frames and additional temporal filtering. Conclusion: We found that temporal glottal midline detection using a dual decoder architecture together with keypoint estimation allows accurate midline prediction. Clinical impact: We show that our proposed architecture allows stable and reliable glottal midline predictions ready for clinical use and analysis of symmetry measures.
CRIS-Team Scopus Importer:2023-02-10
Keywords: biomedical imaging; Convolution; Decoding; Deep learning; deep learning; deep neural networks; glottis; Image segmentation; Laryngeal endoscopy; midline; Neural networks; Three-dimensional displays; Videos